Can we use old Harris and Bennedict formula for determine resting energy expenditure in anorexia nervosa? Probably not! - Correia, Carla (2019)
Background: Anorexia Nervosa (AN) is characterized by a severe restriction of energy intake that results in a significantly low body weight reflecting depletion in body compartments, as well as a decrease in Resting Energy Expenditure (REE). Overfeeding is of great concern when feeding these patients to establish an adequate amount of energy will assure recovery of nutritional status and prevent complications. The aim of this study was to investigate the relationship between measured and estimated REE values.